Occurrence of severe rotavirus gastroenteritis in children younger than three years of age before and after the introduction of rotavirus vaccine: a prospective observational study in four pediatric clinics in Shibata City, Niigata Prefecture, Japan - Tomohiro Oishi; Masamichi Matsunaga; Tokushi Nakano; Shoji Sudo; Hiroaki Kuwajima; Shuko Tokuriki; Shibata RVGE Study (Taylor & Francis Group, 2020)
In Japan, rotavirus (RV) vaccines have already been introduced but not used for universal vaccination as of 2018. Therefore, we identified cases of severe rotavirus gastroenteritis (RVGE) in children younger than three years of age and investigated the occurrence of infection before and after the introduction of RV vaccines. An ecological study through prospective surveillance was conducted in four pediatric clinics in Shibata City, Niigata Prefecture, Japan, during the 2011 to 2018 RVGE epidemic seasons. We divided the study period into three eras: pre-vaccine introduction era (2011), low-mid coverage transitional era (2012 to 2014, RV vaccine coverage rate: 32.9-56.5%), and high coverage plateau era (2015 to 2018, 67.7-81.7%). In this study, the incidence rate of severe RVGE was significantly lower in the plateau era than in the pre-vaccine introduction and transitional eras. Furthermore, the hospitalization rate due to RVGE in Shibata City was lower in the plateau era than in the pre-vaccination introduction and transitional eras. The number of hospitalizations due to RVGE in subjects who required or did not require intravenous rehydration at the pediatric clinics significantly decreased with the increase in vaccine coverage rates by more than 70% in the plateau era.